KECEMASAN IBU HAMIL TENTANG PELAYANAN ANTENATAL CARE DI ERA PANDEMI COVID-19 - Kandace Sianipar; Juneris Aritonang; Wilda Wahyuni Siregar (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2021)
The provision of maternal services during the pandemic needs to be a concern to avoid an increase in maternal morbidity and mortality, especially at this time there are restrictions on maternal health services in the form of anxiety during pregnancy during the Covid19 pandemic. The type of research used in this study is descriptive which aims to determine the anxiety of pregnant women about ante natal care services in the era of the Covid-19 pandemic at the Bandar Khalipah Health Center in 2020. The population in this study were all pregnant women who did ANC checks in the Bandar Khalipah Health Center area. The sampling technique used in this study was accidental sampling (sampling when the study was conducted) totaled 34 people. The results of the study found that the majority of respondents had mild anxiety (44%) about Ante Natal Care services in the Covid-19 pandemic era. From the results of this study, pregnant women should seek correct information about safe pregnancy during the Covid-19 pandemic so that they can change the anxiety of pregnant women about Ante Natal Care services in the Covid-19 pandemic era assisted by health workers in health education activities.